Inositol in the MAnaGemENt of abdominal aortic aneurysm (IMAGEN): Study protocol for a randomised controlled trial - Rowbotham, S.; Pinchbeck, J.; Anderson, G.; Bourke, B.; Bourke, M.; Gasser, T.; Jaeggi, R.; Jenkins, J.; Moran, C.; Morton, S.; Reid, Christopher; Velu, R.; et al. (BioMed Central, 2017)
© 2017 The Author(s). Background: An abdominal aortic aneurysm (AAA) is a focal dilation of the abdominal aorta and is associated with a risk of fatal rupture. Experimental studies suggest that myo-inositol may exert beneficial effects on AAAs through favourable changes to biological pathways implicated in AAA pathology. The aim of the Inositol in the MAnaGemENt of abdominal aortic aneurysm (IMAGEN) trial is to assess if myo-inositol will reduce AAA growth. Methods/design: IMAGEN is a multi-centre, prospective, parallel-group, randomised, double-blind, placebo-controlled trial. A total of 164 participants with an AAA measuring = 30 mm will be randomised to either 2 g of myo-inositol or identical placebo twice daily for 12 months. The primary outcome measure will be AAA growth estimated by increase in total infrarenal aortic volume measured on computed tomographic scans. Secondary outcome measures will include AAA diameter assessed by computed tomography and ultrasound, AAA peak wall stress and peak wall rupture index, serum lipids, circulating AAA biomarkers, circulating RNAs and health-related quality of life. All analysis will be based on the intention-to-treat principle at the time of randomisation. All patients who meet the eligibility criteria, provide written informed consent and are enrolled in the study will be included in the primary analysis, regardless of adherence to dietary allocation. Discussion: Currently, there is no known medical therapy to limit AAA progression. The IMAGEN trial will be the first randomised trial, to our knowledge, to assess the value of myo-inositol in limiting AAA growth. Trial registration: Australian New Zealand Clinical Trials Registry, ACTRN12615001209583. Registered on 6 November 2015.